2020
DOI: 10.1177/1046496420967764
|View full text |Cite
|
Sign up to set email alerts
|

Communication in Transactive Memory Systems: A Review and Multidimensional Network Perspective

Abstract: The comprehensive review synthesizes 64 empirical studies on communication and transactive memory systems (TMS). The results reveal that (a) a TMS forms through communication about expertise; (b) as a TMS develops, communication to allocate information and coordinate retrieval increases, promoting information exchange; and (c) groups update their TMS through communicative learning. However, direct interpersonal communication is not necessary for TMS development or utilization. Nor do high-quality information-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 99 publications
(202 reference statements)
0
29
0
Order By: Relevance
“…Previous research shows that successful teams use transactive memory systems for storing and retrieving their knowledge (Yan et al, 2021), and externalizing knowledge structures can be a first step toward establishing such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that successful teams use transactive memory systems for storing and retrieving their knowledge (Yan et al, 2021), and externalizing knowledge structures can be a first step toward establishing such systems.…”
Section: Discussionmentioning
confidence: 99%
“…Those software agents can be implemented to take over team communication (cf. Fiore & Wiltshire, 2016;Yan et al, 2021;real-life example: Unite Alarm Agent, AscomUK, 2015). At the highest level of automated team communication, software agents take over team communication by requesting experts and answering requests from other team members.…”
Section: Effects Of Automated Team Communication On Team Processes An...mentioning
confidence: 99%
“…Previous research has shown that teams with a transactive memory system perform better than teams without a transactive memory system (e.g., Austin, 2003;Hinsz et al, 1997;Lewis, 2003Lewis, , 2004. As a transactive memory system leads to high interdependence among team members, they must communicate with each other by requesting other experts in their team (Yan et al, 2021). For successful team communication (i.e., less information seeking about the experts and few mistakes in requesting experts), the importance of a meta-knowledge as a directory of "who knows what" that stores knowledge about the expertise of other team members has been emphasized Faraj & Sproull, 2000;Wegner, 1987Wegner, , 1995.…”
mentioning
confidence: 99%
“…Measuring the emotions of team members and, at the same time, the information elaboration of their teams seems promising because team members in positive rather than negative moods are more willing and open to share the information and expertise that only they possess (e.g., Dietz et al, 2017; Pfaff, 2012; Pillay et al, 2020). These informational exchanges then also facilitate the development of TMS (Yan et al, 2021).…”
Section: Future Research Agendamentioning
confidence: 99%